ANALISIS KUALITAS PELAYANAN PADA ATRAKSI WISATA MANGROVE DESA WISATA BUDO - Gumirot, Rivaldo Alfa; Takaendengan, Mita E.; Lewan, Yurike (PolimdoSains, 2025)
Tourism is an important sector in the Indonesian economy, including in North Sulawesi, with theMangrove ecotourism of Budo Village which has great potential. However, the quality of service andhospitality at this tourist attraction still needs to be improved to attract tourists. This study aims toanalyze the quality of service and hospitality at the Budo Village Mangrove tourist attraction, andprovide recommendations for necessary improvements. The research method used is a qualitativeapproach with a descriptive design. Data were collected through observation, interviews, anddocument studies. Researchers conducted interviews with 30 tourists who had visited, and made directobservations at the location. Indicators used to analyze service quality include five indicators, namelytangible, reliability, assurance, empathy, and responsiveness, while hospitality is analyzed throughpolite, kind, and friendly attitudes. The results showed that the quality of service at the Budo VillageMangrove tourist attraction was adequate, but there were still shortcomings, especially in terms ofcleanliness and speed of service. Tangible and reliability indicators show that facilities are good, butwaste management and food delivery time need to be improved. Hospitality is generally good, but thefriendly attitude of reception staff and cashiers still needs to be improved. The researcher alsofound that the manager's attention to visitors was lacking, which impacted the tourist experience.The conclusion of this study is that although Budo Village Mangrove Tourism attraction has providedsatisfactory services, there are still some aspects that need to be improved to enhance the touristexperience. Suggestions for managers include improving cleanliness, training staff to improve friendlyattitudes, and providing security tools. Future research is recommended to expand the scope ofvariables studied and use quantitative methods to gain a more comprehensive understanding.